2000
DOI: 10.1093/pubmed/22.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a community-based intervention to increase breastfeeding prevalence

Abstract: As the impact of the intervention was not sustained even for the modest duration of 6 weeks postnatally, it would be premature to justify widespread use of peer support programmes to increase the prevalence of breastfeeding in socially disadvantaged communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 12 publications
5
81
1
1
Order By: Relevance
“…The decision to continue breast feeding or stop it depends upon a variety of factors. These include the mother's intention to breastfeed, the counseling and support received from health workers and peers, the social, cultural and economical background as well as whether the mother works outside home [3,6,7,8,14,20,21]. Identification of factors, both maternal and neonatal, that adversely affected breastfeeding in perinatal period would help us to pay more attention to these 'high risk' mother-infant pairs and provide them more focused counseling and support.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to continue breast feeding or stop it depends upon a variety of factors. These include the mother's intention to breastfeed, the counseling and support received from health workers and peers, the social, cultural and economical background as well as whether the mother works outside home [3,6,7,8,14,20,21]. Identification of factors, both maternal and neonatal, that adversely affected breastfeeding in perinatal period would help us to pay more attention to these 'high risk' mother-infant pairs and provide them more focused counseling and support.…”
Section: Discussionmentioning
confidence: 99%
“…Peer counselling to promote breast-feeding Peer counsellors had a significant effect on breast-feeding rates and duration Level I -fair 13 Level I -poor 20 Level II-1 -poor [29][30][31][32] There is fair evidence to recommend peer counselling to promote initiation and maintenance of breast-feeding B recommendation…”
Section: A Recommendationmentioning
confidence: 99%
“…In addition, the use of peer counsellors improved breast-feeding rates and duration, and these types of programs may represent a cost-effective alternative to professionally delivered services, especially in locations or settings where professional services are scarce or not available. 13,20,[29][30][31][32] The CTFPHC recommends against the use of written materials (which have not been shown to be effective when used alone, 16,19,22,26,[33][34][35][36] although no harm was demonstrated) and commercial discharge packages (which have been shown to decrease breast-feeding rates). 37 Unfortunately, advice from a woman's primary clinician (such as family physician, obstetrician or midwife) has not been sufficiently evaluated, and a research gap remains in this area.…”
mentioning
confidence: 99%
“…The results of the Canadian study 277 were not replicated in a study in a deprived area of the UK; McInnes et al 277 found that increases in breastfeeding at birth were not maintained at 6 weeks, despite peer support. The control arm in the Canadian study reported a rate of breastfeeding that is greater than the 2005 UK average.…”
Section: Discussionmentioning
confidence: 89%